2022
DOI: 10.1155/2022/5976155
|View full text |Cite|
|
Sign up to set email alerts
|

A New Generation of ResNet Model Based on Artificial Intelligence and Few Data Driven and Its Construction in Image Recognition Model

Abstract: The paper proposes an A-ResNet model to improve ResNet. The residual attention module with shortcut connection is introduced to enhance the focus on the target object; the dropout layer is introduced to prevent the overfitting phenomenon and improve the recognition accuracy; the network architecture is adjusted to accelerate the training convergence speed and improve the recognition accuracy. The experimental results show that the A-ResNet model achieves a top-1 accuracy improvement of about 2% compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…25 The input images of the ResNet model are processed through a convolutional layer, a max-pooling layer, and several residual blocks, then with an average polling layer and fully connected layer, finally result in an output vector of class probabilities. 26 Kazuma and colleagues performed a study using ResNet12 to identify cervical OPLL based on x-rays, they reported a great accuracy of 98.9%. 15 We evaluated the performance of ResNet models with 34-layer, 50-layer, and 101-layer of residual blocks in detecting OPLL with MRI, and we obtained a higher accuracy in those with more residual connection layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The input images of the ResNet model are processed through a convolutional layer, a max-pooling layer, and several residual blocks, then with an average polling layer and fully connected layer, finally result in an output vector of class probabilities. 26 Kazuma and colleagues performed a study using ResNet12 to identify cervical OPLL based on x-rays, they reported a great accuracy of 98.9%. 15 We evaluated the performance of ResNet models with 34-layer, 50-layer, and 101-layer of residual blocks in detecting OPLL with MRI, and we obtained a higher accuracy in those with more residual connection layers.…”
Section: Discussionmentioning
confidence: 99%
“…The ResNet won the ImageNet Large Scale Visual Recognition Challenge by training deeper networks while maintaining fast convergence times 25 . The input images of the ResNet model are processed through a convolutional layer, a max-pooling layer, and several residual blocks, then with an average polling layer and fully connected layer, finally result in an output vector of class probabilities 26 . Kazuma and colleagues performed a study using ResNet12 to identify cervical OPLL based on x-rays, they reported a great accuracy of 98.9% 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The test results will be stored and will be used for evaluation and conclusions at a later stage. [35]. ResNet 9 architecture, which has 9 layers, can be seen in Figure 3.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%